2019
DOI: 10.1002/smtd.201900383
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Newtonian Fluid State K–Na Alloy for a Stretchable Energy Storage Device

Abstract: Potassium–sodium alloy (KNA) is defined as an attractive candidate for energy storage devices in space probes. Nevertheless, high surface tension and fluidity of KNA make the electrode difficult to shape which results in unstable electrochemical properties. In this contribution, a low surface tension and paintable non‐Newtonian fluid state KNA and Super P composite (KNA@C) fabricated by a simple stirring strategy is reported. The formation of hydroxides in the KNA@C composite gives rise to stable liquid alloy–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 55 publications
0
37
0
Order By: Relevance
“…Accordingly, Tu et al synthesized a non‐Newtonian fluid state Na/K alloy and super P composite (KNA@C) with decreased surface tension using a simple stirring strategy (Figure 11d). [ 120 ] Non‐Newtonian fluid state is an intermediate state, which has reduced liquidity, increased adhesion, better flexibility, and ductility compared to that of liquids. Therefore, the high surface tension and poor wettability of the Na/K alloy were changed by tuning it into a non‐Newtonian fluid substance, which can be proved by the strong adhering ability for sea snail, glass fiber, and graphite anode (Figure 11e).…”
Section: K Metal Anodementioning
confidence: 99%
“…Accordingly, Tu et al synthesized a non‐Newtonian fluid state Na/K alloy and super P composite (KNA@C) with decreased surface tension using a simple stirring strategy (Figure 11d). [ 120 ] Non‐Newtonian fluid state is an intermediate state, which has reduced liquidity, increased adhesion, better flexibility, and ductility compared to that of liquids. Therefore, the high surface tension and poor wettability of the Na/K alloy were changed by tuning it into a non‐Newtonian fluid substance, which can be proved by the strong adhering ability for sea snail, glass fiber, and graphite anode (Figure 11e).…”
Section: K Metal Anodementioning
confidence: 99%
“…[1][2][3] To solve these issues, intermittent electricity generation (such as solar and wind power sources) and grid-scale energy storage density in full cell and unsatisfactory cycle stability. Recently, alloy-based material [16,17] has attracted much attention due to higher capacity, suitable working potential, and earth abundance, mainly including P, Sn, Sb, Bi, Si, Ge, and its oxides, sulfides, selenides, and phosphides, as shown in Figure 1. Qian and co-workers [18] reported a hierarchical P/carbon nanotubes (CNTs)@rGO composite, exhibiting a high reversible capacity of 2113 mAh g −1 at 0.2C and long-cycle stability over 500 cycles.…”
Section: Introductionmentioning
confidence: 99%
“…[14] All the abovementioned limitations can be overcome or reduced if dendrite growth/breakage can be prevented during the deposition/ dissolution process. Many studies have been reported on the construction of dendrite-free metal anodes: a) fabrication of modified electrodes or metal substrate surfaces, [15][16][17][18][19][20][21][22][23][24] b) synthesis of new electrolytes, [25][26][27][28][29] c) use of solid electrolytes, [22,[30][31][32] and d) improvement of the electrode-electrolyte interface. [9,15,33,34] However, these studies have rarely focused on the properties, such as the stability of dendrites during charging and discharging, of dendrites.…”
mentioning
confidence: 99%